Breaking Barriers: Women's Empowerment Through Online Education Platforms - Khaliqi, Horia; Qaderi, Karishma; Akrami, Sonya; Akrami, Khatera; Quraishi, Tamanna (Lembaga Riset dan Inovasi Masyarakat Madani, 2024)
This study investigates the intersection of online education platforms and women's empowerment through a mixed-methods approach. The research addresses the problem of gender disparities in education by examining the role of digital technologies in promoting women's empowerment. The purpose of the study is to comprehensively explore various aspects of online education platforms and their impact on women's empowerment, focusing on factors examined, primary study focuses, aspects of women's empowerment, policy objectives, institutional support, and challenges in gender equality policies implementation. The research methodology involves a population consisting of students, educators, policymakers, and stakeholders in online education, with a targeted sample size of 160 participants. A structured survey questionnaire is utilized for data collection, employing both quantitative and qualitative analysis techniques. Quantitative data analysis includes descriptive statistics to summarize survey responses, while qualitative data interpretation involves thematic analysis of open-ended responses and interviews. The findings provide insights into the effectiveness of digital literacy programs, challenges faced, and the impact of policy interventions on women's empowerment. The study contributes to the existing literature by offering a comprehensive understanding of the multifaceted dynamics between online education platforms and women's empowerment, with implications for policy, practice, and future research directions.